Diksi dalam Lirik Lagu Ngilmu Pring Karya Jogja Hiphop Foundation: Kajian Stilistika - Kurnianingrum, Aprilia (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2024)
The purpose of this study was to determine the use of diction and its function in the lyrics of the song Ngilmu Pring by the Jogja Hiphop Foundation. This study used a descriptive qualitative method. The research data are in the form of phrases, words, and sentences in the lyrics of the song Ngilmu Pring by the Jogja Hiphop Foundation. Data collection techniques used in this study used inventory, read-listening, and recording techniques.